Analysis of Testamentary Regulations in Islamic Law: A Study of Legal and Practical Aspects - Tolhah Toha Nawawi (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes the regulation of wills in Islamic law with a focus on legal and practical aspects. A will is an instrument in the distribution of inherited assets regulated by Islamic law, which has special provisions regarding limitations, recipients and implementation. This study uses a normative research method with a juridical-theological approach to explore the legal basis of wills in the Qur'an, Hadith, and fatwas of scholars. In addition, this study also reviews the practice of implementing wills in Muslim society, including the challenges that arise in their implementation. The results of this study indicate that a will in Islamic law has a significant role in distributing inheritance fairly, especially for parties who are not included in the list of heirs. Based on an analysis of Islamic legal sources, both from the Qur'an, Hadith, and the opinions of scholars, it was found that a will not only functions as a form of social concern, but also as a legal instrument that grants rights to certain individuals without violating the principle of justice in the distribution of inheritance. This study also emphasizes that the implementation of a will must meet certain requirements, such as the existence of ijab and qabul, a maximum limit of one third of the inheritance, and an agreement with the heirs if the amount exceeds this limit. In addition, wills have been proven to have a positive impact in preventing conflict among heirs and ensuring that the assets left behind are used properly in accordance with the principles of justice in Islam.